The situation of persons with vision impairments as voters in Poland - Radosław Zych (Acta Iuris Stetinensis, 2024)
The subject of this article touches upon an important aspect – realization of the voting right by a person with disabilities involving a vision impairment (hereinafter: persons with vision impairments). The aim of this discussion is to answer the question of whether the Polish electoral law requires amendment with regard to institutions associated with the organization of the electoral process and which are a facilitation for voters with vision impairments. The author analyses questions of the realization of the voting right defined in the title by persons with vision impairments. Statistics and real-life examples are quoted, including results of an interview with a University of Szczecin student with visual impairments, to illustrate real possibilities to exercise voting rights by such persons. This discussion relates to the subject matter important from the point of view of social relations. The conclusions present de lege ferenda postulates for amending the law, which would guarantee effective implementation of voting rights by persons with vision impairments.